2018
DOI: 10.1177/1046496418755510
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Complexity, Participation, and Agreement in Group Discussions

Abstract: This study tested status-contingency theory and conversion theory on a task in which members made ordered judgments instead of dichotomous judgments. In groups, participants discussed whether “under God” should be in the pledge of allegiance and reached consensus on an ordered scale. Members’ contributions were scored for integrative complexity. In groups with more dispersion of opinion, members with opinions less discrepant from other group members did not have higher integrative complexity than members with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous research showed that the complexity of group-level cognitive structures is influenced by the quality of within-group interactions (Curşeu et al, 2012; Curşeu et al, 2007) and, in turn, has a positive impact on group performance (Curşeu & Schruijer, 2010). Moreover, minority dissent or the open disagreement with the opinions expressed by the majority seems to enrich the cognitive repertoire of the group (Curşeu et al, 2012; Curşeu, Schruijer, & Fodor, 2017; Van Swol, Carlson-Hill, & Acosta Lewis, 2018). Normative interventions or interaction rules that stimulate the expression of diverse opinions and help the groups to achieve consensus foster the emergence of complex collective cognitive structures (Curşeu & Schruijer, 2012).…”
Section: Number Of Group Arguments and Gccmentioning
confidence: 99%
“…Previous research showed that the complexity of group-level cognitive structures is influenced by the quality of within-group interactions (Curşeu et al, 2012; Curşeu et al, 2007) and, in turn, has a positive impact on group performance (Curşeu & Schruijer, 2010). Moreover, minority dissent or the open disagreement with the opinions expressed by the majority seems to enrich the cognitive repertoire of the group (Curşeu et al, 2012; Curşeu, Schruijer, & Fodor, 2017; Van Swol, Carlson-Hill, & Acosta Lewis, 2018). Normative interventions or interaction rules that stimulate the expression of diverse opinions and help the groups to achieve consensus foster the emergence of complex collective cognitive structures (Curşeu & Schruijer, 2012).…”
Section: Number Of Group Arguments and Gccmentioning
confidence: 99%